Nano-phytoremediation technologies for groundwater contaminates : emerging research and opportunities - Chaudhary, Khushboo, 1989-; Khan, Suphiya, 1976-; Saraswat, Pankaj Kumar, 1976- (Engineering Science Reference, an imprint of IGI Global, 2020)
"This book explores phytoremediation and some experimental methods used in life science laboratories. It also examines various heavy metals and non-metals and their effect on remedial approaches"-- Provided by publisher.
Keywords: Phytoremediation.; Groundwater -- Purification.; Groundwater -- Pollution.; Heavy metals -- Environmental aspects.; elektronické knihy; electronic books